Sickle beta zero thalassemia and acute chest syndrome in pediatric: Case report (Research, Society and Development, 2024)
The objective of this article is to report the case of a 5-year-old male patient diagnosed with Sickle Beta Zero Thalassemia. An inherited disease that affects the hemoglobin of red blood cells, causing the formation of hemoglobin S (sickle cell) and thalassemia.  The presence of "zero" indicates the absence of normal hemoglobin in the blood. This condition leads to the sickle-shaped deformation of red blood cells, making their circulation in blood vessels difficult, generating complications, including acute chest syndrome. It is possible to recognize this rare disease by its clinical presentation and with the help of the laboratory. A diagnosis was established in the patient based on clinical findings such as diagnostic images, complete blood count, peripheral blood smear and hemoglobin electrophoresis and subsequent evaluation by the pediatric hematology specialist. Clinical genetics is increasingly relevant in today's medicine, and it is essential that primary care (PC) professionals become familiar with its concepts. The correct identification of these patients ensures adequate genetic counseling and the implementation of regular clinical controls. This allows for early preventive intervention and addressing health problems before they fully develop.